A role for trunk function in elite recumbent handcycling performance? - Muchaxo, R.; De Groot, S.; Kouwijzer, I.; van der Woude, L.; Janssen, T.; Nooijen, C. F. J. (Journal of Sports Sciences, 2021)
Handcycling classification considers trunk function, but there is limited scientific evidence of trunk involvement in recumbent performance. This study investigated the association between trunk function and recumbent handcycling performance of athletes without upper-limb impairments (H3-H4 sport classes). The study was divided into two parts. First, 528 time-trial results from 81 handcyclists with spinal cord injury (SCI) were obtained between 2014 and 2020. Average time-trial velocity was used as performance measure and SCI level as trunk function determinant. Multilevel regression analysis was performed to analyse differences in performance among SCI groups while correcting for lesion completeness, sex, and age. Second, in 26 handcyclists, standardised trunk flexion strength was measured with a handheld dynamometer. Peak and mean power-output from a sprint test and time-trial average velocity were used as performance measures. Spearman correlations were conducted to investigate the association between trunk strength and performance. Results showed that the different SCI groups did not exhibit significant differences in performance. Furthermore, trunk flexion strength and performance exhibited non-significant weak to moderate correlations (for time-trial speed: rs = 0.36; p = 0.07). Results of both analyses suggest that trunk flexion strength does not seem to significantly impact recumbent handcycling performance in athletes without upper-limb impairments.